Ethnicity Matters in Healthcare - Singh, Gurmukh (Archives of Clinical and Biomedical Research, 2025)
There is increasing emphasis on excluding race in consideration of healthcare matters. This is mostly due to the history of discrimination based on race/ethnicity/social status etc. However, ethnicity has implications for the prevalence of disorders and responses to treatment. While excluding race/ ethnicity from consideration is a noble effort, it runs counter the philosophy of precision medicine demanding individualized care for each person. The opinion expressed in this article makes a case for including consideration of ethnicity as it may be relevant to the care of an individual, without using it to adversely discriminate a person from receiving optimal healthcare.